If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 14 = a + 83 Reorder the terms: 14 + 4a = a + 83 Reorder the terms: 14 + 4a = 83 + a Solving 14 + 4a = 83 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 14 + 4a + -1a = 83 + a + -1a Combine like terms: 4a + -1a = 3a 14 + 3a = 83 + a + -1a Combine like terms: a + -1a = 0 14 + 3a = 83 + 0 14 + 3a = 83 Add '-14' to each side of the equation. 14 + -14 + 3a = 83 + -14 Combine like terms: 14 + -14 = 0 0 + 3a = 83 + -14 3a = 83 + -14 Combine like terms: 83 + -14 = 69 3a = 69 Divide each side by '3'. a = 23 Simplifying a = 23
| 10x-8=5x+4 | | Y*6+109=Y*11-11 | | -4(-6)=(-9+y)(-2) | | (8y+9)(8y-9)= | | -3.128*7000000= | | 156-4x=32x+16 | | 17-7x=132-28x | | 215-2x=43x+20 | | 3-x=2x-3 | | 9x-7=5(2x-4) | | 6x-7=73-10x | | -10x-2x=14-8x | | 2(a+3)+3(a-1)= | | -3(4x+1)+3= | | 12.6x+5.8=9x-4.3 | | 4x+7=107-4x | | 8+(x-3)=19 | | 5x+7x=39 | | -19-2x=13-2x | | 8+(x+3)=19 | | 66-3x=42x-16 | | 59-3x=33x+15 | | x*6+126=11-14 | | t^2-9t-10=0 | | X=37.56+0.25x | | C=37.56+0.25x | | 12.6+5.8=9x-4.3 | | (-2)-3y=-6 | | 34a-4(5a+2)=32 | | 93-3x=33x+17 | | 14-7x=24-14x | | 5x^2+8x-2=0 |